Sound absorption of a perforated panel backed with perforated porous material: Energy dissipation of Helmholtz resonator cavity. (15th February 2023) - Liu, Xuewei; Liu, Maolin; Xin, Fengxian
Graphical abstract: Highlights: A theoretical model is developed for the sound absorption of a perforated rigid panel backed with gradually perforated porous material. A finite element model is also established, whose results fit well with the developed theoretical model. The metamaterial has been theoretically and numerically demonstrated good sound absorption for noise at low frequencies. The effects of key structure parameters on sound absorption are systematically explored. This new resonance metamaterial provides another avenue for the design of low-frequency sound absorbers. Abstract: A new type of low-frequency sound absorbing Helmholtz resonator is proposed, which consists of a perforated rigid panel backed with gradually perforated porous material. A theoretical model is developed by dividing the structure into a multi-layer system by using the double porosity theory, which is verified by finite element simulations and experimental measurements. The sound absorption performance of the proposed acoustic metamaterial is studied by applying the theoretical model and numerical model, where the influences of the perforation diameter, panel thickness, back cavity shape and static flow resistivity of the porous material matrix on sound absorption are discussed. The results show that this new metamaterial has better sound absorption performance than the perforated panel and the perforated porous material. Finite element simulations show that this new acoustic metamaterial absorbs sound energy almost entirely through Helmholtz cavity resonance, which accelerates the diffusion of sound into the porous material for dissipation. An energy dissipation compensation mechanism is found between the perforated panel and the perforated porous material, which enables the metamaterial to always achieve near-perfect sound absorption performance over a wide range of neck diameters. This new resonance metamaterial provides another avenue for the design of low-frequency sound absorbers.